PERAN KOMUNIKASI KELUARGA TERHADAP KONSEP DIRI ANAK USIA DINI - Magta, Mutiara (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
Abstract.  Self-concept is a picture of a person based on his/her knowledge, expectation and judgment about him/herself through the various experiences. The development of self-concept that a person learn from childhood will lead them to self-actualization as a manifestation of their existence in social life. The first experience of a child's life takes place in the family. Interactions between family members affect the way a person views him and his surroundings. Various forms of communication provide a wealth of experience in shaping positive or negative self-concept Keywords : self concept, communication, family, early childhood